Factors That Influence for Pratical Clinical Skill I-IV During Training in The School of Midwife, 2021 - Barreto Amaral, Meriana; Guterres Correia, Avelino; Deus, Elisa de; Julieta Geri De Sena Amaral, Saturnina; Freitas Moreira, Adriano; Soares, Miguel; Almeida Oqui, Serafino de (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Education is a faciliting process of learning, or ocassion of knowledge, ability, value, faith and also incluides the method of education. To reduce maternal mortality rate with 55/100.000 nv and decrease to 218/100.000nv, IMR 44/100.000 Ib, NMR  22/1000 nv in Timor- Leste. Objetive: To know the factors that influence the clinical pratical ability during training at the school of Midwife the Faculty of Medicine Health Science UNTL, in the year 2021. Method: This reseach method uses quantitative analytical methods and cross sectional approximation. Instruments used to collect questionaire data. Analyze this Univariate,Bivariate data and use chi-Square statistics. Results and Discussion: The factors of clinical pratical ability are 30 (78.9%) with p-value (0.000). Students who have minimal atittude and ability are 20 (100) with p-value (0.000). Students who have motivation study and minimal skill are 17 (67.7%) with p-value (0.098). Students who have emotional and minimal skill are 25 (100%) with p-value (0.000).Students who have intellectual capacity and minimal ability are 25 (100%) with p-value (0.000). Conclusion: This study indicate the factors that have an influence on clinical pratical ability are influence students experince, students atittude, sdendents motivation, students emotional and intellectual capacity students